Efficient CELI endonuclease production in Nicotiana benthamiana through transient expression and applications in detections of mutation and gene editing events. (July 2020) - Yao, Xue-Feng; Wu, Shengyang; Guo, Lei; Liu, Chun-Ming
Highlights: Recombinant CELI endonuclease was produced in bulk from tobacco ( N. benthamiana ) through Agrobacterium-mediated transient expression. The GFP-CELI-His purified by affinity column showed improved efficiency and mismatch cleavage activity to that of the crude CELI purified from celery. The optimized CELI reaction buffer with Mn 2+ and DTT provided in this study allows to effectively detect mutation and gene editing events including small substitutions, deletions and insertions in genomes. The high mismatch detection sensitivity makes possible to perform TILLING screening in 1/32 pooled samples. Abstract: Rapid and low-cost methods of detecting mutations and polymorphisms are crucial for genotyping applications including mutagenesis and gene editing. S1 family endonucleases such as T7E1, EndoV and CELI can potentially be used in enzymatic mismatch detection. Among them, CELI has been shown to be effective in detecting mutations in Targeting Induced Local Lesions IN Genomes (TILLING). However, current method of CELI purification from celery is laborious, and challenging for many non-biochemical laboratories, and the presence of post-translational modifications hinders efficient production of the enzyme in E. coli . Here, we report an efficient system for bulk production of enzymatically active CELI endonuclease through transient expression in a model plant Nicotiana benthamiana . We also optimized the reaction buffer, by additions of Mn 2+ and DTT, with enhanced mismatch cleavage activity. Using the new CELI production and reaction system, we were able to routinely detect mismatches in 1/32 mixed mutant and wildtype DNA samples. We believe the newly established system has many applications in characterization of mutations occurred in natural variations, mutagenized populations and gene editing.